Preparation and Characterization of High Modulus Agent Modified Asphalt and Its High Modulus Mixture - Shi-Zhong Mi; Yong-Xiang Li; Hai-Wei Zhang (Advances in Materials Science and Engineering)
Improving the high-temperature stability and water damage resistance of asphalt pavements has always been a priority. This study proposed a composite high modulus modifier with rock asphalt and nanopolymer as main materials (HRMA) to prepare the high modulus asphalt mixture for their excellent rutting resistance. Moreover, its modification effect and modification mechanism were studied. The effect of HRMA content on the rheological performance of asphalt was investigated using Brookfield rotational viscosity, dynamic shear rheometers (DSR), and bending beam rheometers (BBR). Their modification mechanisms were revealed by Fourier Transformation Infrared Spectroscopy (FTIR). Besides, the properties of the mixtures were studied in various laboratory tests and compared with the 90# asphalt mixture and SBS asphalt mixture. Some of these included the rutting test, the bending test, the Marshall immersion test, and the freeze-thaw indirect tension test. The results indicated that with the increase of HRMA content, the deformation resistance of the asphalt mixture under high-temperature conditions was significantly improved, and the temperature sensitivity was changed. However, the crack resistance of its asphalt mixtures under low temperature was reduced due to the lower ductility of HRMA-modified asphalt. The recommended HRMA content was 21.8% of the asphalt, combining performance and construction cost.